2021
DOI: 10.3390/molecules26133997
|View full text |Cite
|
Sign up to set email alerts
|

A Compendium of the Most Promising Synthesized Organic Compounds against Several Fusarium oxysporum Species: Synthesis, Antifungal Activity, and Perspectives

Abstract: Vascular wilt caused by F. oxysporum (FOX) is one of the main limitations of producing several agricultural products worldwide, causing economic losses between 40% and 100%. Various methods have been developed to control this phytopathogen, such as the cultural, biological, and chemical controls, the latter being the most widely used in the agricultural sector. The treatment of this fungus through systemic fungicides, although practical, brings problems because the agrochemical agents used have shown mutagenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 174 publications
0
3
0
Order By: Relevance
“…Certain authors have assessed the activity against FOX of those derivatives and observed inhibition halos ranging from 28 to 32 mm, demonstrating better activity compared to the positive control nystatin, which exhibited a 23 mm halo. 40 Moreover, Xie et al 41 have reported the in vivo and in vitro biological activity of some molecules containing a benzofuran ring against other phytopathogenic fungi such as Colletotrichum iagenarium and Erysiphe graminis . They obtained data comparable to the positive control enoxastrobin , showing inhibition up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Certain authors have assessed the activity against FOX of those derivatives and observed inhibition halos ranging from 28 to 32 mm, demonstrating better activity compared to the positive control nystatin, which exhibited a 23 mm halo. 40 Moreover, Xie et al 41 have reported the in vivo and in vitro biological activity of some molecules containing a benzofuran ring against other phytopathogenic fungi such as Colletotrichum iagenarium and Erysiphe graminis . They obtained data comparable to the positive control enoxastrobin , showing inhibition up to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…typically infect plant vasculature, disrupting water and nutrient transport to tissues, while also producing toxic secondary metabolites that add to their virulence, cumulatively leading to wilting, rot of various plant organs, and eventually death. In particular, Fusarium oxysporum causes foliar blight, a vascular disease that can kill plants and result in major production losses [4][5][6]. Fusarium solani is a causative pathogen of root rot disease in a variety of crops, and fruit rot in a subset of hosts [7].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are naturally occurring spliceosome modulators that exhibit interesting structural features and are potential anti-cancer agents. In addition, the review by Borrego-Muñoz et al [ 9 ] illustrates the use of organic synthesis for the preparation of agrochemical agents, presenting a compendium of the recent synthetic methodologies employed for the preparation of antifungal compounds against Fusorium oxysporium species. These phytopathogens cause vascular wilt and substantial economic losses in agriculture.…”
mentioning
confidence: 99%